Longitudinal NMR-based Metabolomics Analysis of Male Mountain Ultramarathon Runners: New Perspectives for Athletes Monitoring and Injury Prevention - Matthieu Schoumacher; Julie Nguyen; Eric Brevers; Arianna Cirillo; Manon Campas; Elodie Grifnée; Justine Demeuse; Loreen Huyghebaert; Philippe Massonnet; Thomas Dubrowski; Joy Ledeck; Stéphanie Peeters; et al. (Sports Medicine - Open, 2025)
Abstract Background The aim of this study was to explore how a metabolomic approach could provide valuable information on changes in the athletes' metabolome during a mountain ultramarathon race. To achieve this goal, we established a longitudinal cohort of athletes enrolled in the TOR des Géants, a 330 km mountain ultramarathon with 24,000 m of elevation gain. Sixteen healthy male athletes (43.9 ± 10.1 years) were recruited, and blood samples were collected at four time points: pre-race, mid-race, post-race and after 72 h recovery. Using a 1H-NMR-based metabolomic approach, we evaluated metabolic changes that occur during both race effort and recovery, and correlated them with functional muscle, cardiac, inflammatory, and renal biomarkers already used in the clinic. The processed data were analyzed using multivariate analysis tools specific to longitudinal study design, and innovative pathway analysis was used for data interpretation. Results Mountain ultramarathon running significantly affected the metabolism and physiology of athletes. Multivariate analysis highlighted specific metabolites and functional biomarkers associated with prolonged exercise. Neither metabolite levels nor biomarker concentrations returned to baseline after 3 days of recovery. Finally, innovative pathway analysis shed light on specific metabolic changes resulting from mountain ultramarathon exercise. Conclusion In this study, we propose an NMR-based metabolomics strategy to assess exercise-associated metabolic changes during and after events such as the Tor des Géants. Using state-of-the-art data representation methods specific to metabolomics analysis, we demonstrated that such a methodology can provide a unique view of the biology associated with such extreme conditions. As this approach provides unique insights into the biology of extreme exercise, it holds promise for the development of new tools for athlete management.